2015
DOI: 10.7763/ijesd.2015.v6.653
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Effect of TiO2 Nano Photocatalysis in the Pretreatment of Seawater Reverse Osmosis Desalination

Abstract: Abstract-Sultanate of Oman is experiencing rapid increase in water demand due industrialization and population growth. Desalination contributes for about 35% of water demand in Oman and almost all desalination plants are based on conventional energy source. Utilization of solar energy in desalination is good option due its abundance availability throughout the year in Sultanate of Oman. In this paper, the effect of titanium dioxide (TiO 2 ) nano photocatalysis for the pretreatment step of reverse osmosis desal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…For this reason, a research effort is underway to discover photocatalysts that can use the sizable visible light power available from the sun. Wide bandgap semiconductor catalysts have been modified in the attempt to harvest visible light and disinfect water, using a variety of techniques: (i) Transition-metal semiconductor doping with 148 (iv) Introduction of organic dyes and polymers sensitive to visible light on the nanostructured catalyst surface; 104 (v) Introduction of defect states in the midbandgap region of the semiconductor; 149 (vi) Addition on plasmonic metal nanoparticles for visible-range surface-plasmon resonance enhanced photo catalysis. 150 Reference.…”
Section: •-mentioning
confidence: 99%
“…For this reason, a research effort is underway to discover photocatalysts that can use the sizable visible light power available from the sun. Wide bandgap semiconductor catalysts have been modified in the attempt to harvest visible light and disinfect water, using a variety of techniques: (i) Transition-metal semiconductor doping with 148 (iv) Introduction of organic dyes and polymers sensitive to visible light on the nanostructured catalyst surface; 104 (v) Introduction of defect states in the midbandgap region of the semiconductor; 149 (vi) Addition on plasmonic metal nanoparticles for visible-range surface-plasmon resonance enhanced photo catalysis. 150 Reference.…”
Section: •-mentioning
confidence: 99%
“…Figure 6 shows the output variable's percentage removal efficiencies, depicted with reaction times. The reaction time steadily grew from 0 to 180 minutes before rapidly decreasing to 300 minutes [13]. TOC and COD increase sharply up to 180 min and decrease at 300 min [2].…”
Section: Effect Of Reaction Timementioning
confidence: 95%
“…During the experiments, it was revealed that the absorbance accuracy of H2O2 is dependent on its concentration. Therefore, the efficiency of the water treatment system increases with H2O2 concentration [13].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide is widely studied as a photocatalyst due to its high photocatalytic activity. Furthermore, it is resistant to chemicals, insoluble in water, nontoxic, and inexpensive [ 6 ].…”
Section: Introductionmentioning
confidence: 99%